Kualitas sumber daya manusia sebagai aspek fundamental dalam menunjang perekonomian - Wahid, Wahid; Nawir, Fadliyani; Farhan, Ahmad (Nur Science Institute, 2024)
The significance of the Human Resources (HR) function as a crucial production element is inextricably linked to economic endeavors, with HR providing numerous contributions both broadly and specifically within entrepreneurial contexts. This investigation seeks to evaluate the significance of HR as a pivotal component in bolstering the economy. This research adopts a qualitative methodology, employing a literature review approach that leverages prior data and studies as comparative and foundational material for formulating research findings in alignment with the research objectives. The data amassed originates from Indonesia's Central Statistical Agency (BPS) and encompasses databases of scholarly articles and research, including Google Scholar, Semantic Scholar, ScienceDirect, and JStor. The analytical technique employed for data interpretation is deductive reasoning, aimed at extracting data and information pertinent to the subject matter of this study. The findings of this research indicate that the caliber of proficient HR can enhance economic performance, facilitate sustainable development, and increase competitiveness. Various economic challenges that can be effectively addressed through the presence of skilled HR include unemployment, poverty, and inadequate welfare. The caliber of HR is contingent upon the availability of high-quality education and optimal health conditions.